Vascular corrosion casting of human heart - Reddy, J. Vasudeva; Lokanadham, S. (International Journal of Research in Medical Sciences, 2017)
Variation in the morphological pattern of coronary arteries and their major branches is an important factor in the assessment and treatment of coronary heart disease. Detailed knowledge of the blood supply of the heart is necessary today because of the wider practice of cardiac surgery, and also for better understanding of the anomalous branches, anastomosis and dominance pattern in circulation caused by coronary vasculature. We utilized 80 human heart specimens and found right dominance in 69 specimens, left dominance in 9 specimens and balanced type of circulation in 2 specimens. We observed anastomosis between the major arteries in arteriogram but in vascular corrosion method we did not found because cast substance interpretation to minor vessels is too difficult. The present study acknowledges about Coronary vascular pattern, circulatory dominance of the arteries and by using the vascular corrosion method.